Social Protection is the Essence and Genesis of the Phenomenon - Kuramboyev Makhsudovich (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
this article analyzes issues of anti-poverty and social protection from historical, religious and philosophical perspectives. It is also shown how other religious teachings and philosophical views also played a role in shaping attitudes towards social protection. The article also talks about how social protection systems have perfected with the development of states and the revival and development of these systems in the current period. The article, going deep into the historical and spiritual foundations of social protection issues, confirms its relevance today.